Dimensionamento de estruturas de aço em situação de incêndio - Michele Mendonca Martins (2000)
The fire design of steel structures has just recently called attention frompublic authorities and researchers in Brazil. Starting from researches developed in some universities in 1995, it was made a code about the subject (NBR 14323), published by ABNT in 1999. In this work, the basic concepts of NBR 14323 are presented to the design of steel elements in fire conditions, including fire features, actions and security, fire strength required time, protection of structural elements, procedures involving structural elements temperature increase, design strength and steel features correlation between structural elements and temperature increase. In order to obtain the fire strength required time, anotherBrazilian code published by ABNT in January of 2000 is presented, whichconcerns especially with this subject. So as to illustrate the design in firecondition, one shows the determination of the critical temperature of steelcompression members and beams without lateral or local buckling. Besides, tables and graphics with values of that temperature depending on the boundary and design conditions are presented, also considering the ordinary temperature and the relationship between design effect of actions for the fire situation and the design effect of actions at ordinary temperature. It is also presented a complete numerical example of structural design in fire conditions for a commercial building in order to show the application of the method recommended by NBR14323. At the end, one presents a program in DELPHI. to study the structural design of tensioned beams, compressed, buckled members and members submitted to combined actions in fire conditions and at ordinary temperature.